The coupling of blue emitting carbon dots with Eu3+/Tb3+ co-doped luminescent glasses for utilization in white light emitting diodes - Korkmaz, Ulas; Ozlem, Beyza; Erol, Erdinc; Alas, Melis Ozge; Alturk, Rukan Genc; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (ROYAL SOC CHEMISTRY, 2023)
Lanthanide-doped luminescent glasses have attracted tremendous attention in modern optoelectronic applications, especially for solid-state white light-emitting diodes (WLEDs). Eu3+/Tb3+ co-doped luminescent glasses are well-known to emit intense yellowish-orange light resulting from the energy transfer from green-emitting sensitizer Tb3+ ions to red-emitting activator Eu3+ ions. Obtaining highly efficient blue light from lanthanide ions remains a challenge due to their weak down-converted emission. In this work, we attempt to use the unique characteristics of blue-emitting carbon dots (BCDs), i.e., a broad emission spectrum, ease of synthesis, and high stability, to compensate for this blue light deficiency problem. Correspondingly, a new strategy is proposed by coupling BCDs with Eu3+/Tb3+ co-doped glasses for their potential utilization in WLEDs. Hence, Eu3+/Tb3+ co-doped glasses are prepared in different thicknesses, i.e., 0.8, 1, and 1.5 mm, via the conventional melt-quenching method and subsequently spin-coated with BCDs to achieve adjustable photoluminescence quantum yield (PLQY) values. Ultimately, a proof-of-concept WLED is prepared using a 0.8 mm thick BCD-coated Eu3+/Tb3+ co-doped luminescent glass exhibiting outstanding luminescence performance with a CRI value of 92, a CCT of 4683 K, color coordinates of (x = 0.3299, y = 0.3421), a satisfying PLQY value of 55.58%, and a corresponding LER value of 316 lm W-1 under the excitation of a 375 nm UV LED. BCD-coated Eu3+/Tb3+ co-doped luminescent glasses show excellent stability against photobleaching, temperature variations, and humidity. The findings of this work indicate that the coupling of BCDs with Eu3+/Tb3+ co-doped luminescent glasses holds great potential as a substitute for traditional solid-state lighting sources.
Keywords: ENERGY-TRANSFER; TUNABLE EMISSION; QUANTUM DOTS; EU3+ PHOTOLUMINESCENCE; GREEN; TB3+; PHOSPHORS; RED; ENHANCEMENT; CONVERSION; Chemistry; Physics